Nuclear inclusions of pathogenic ataxin-1 induce oxidative stress and perturb the protein synthesis machinery - Laidou, Stamatia; Alanis-Lobato, Gregorio; Pribyl, Jan; Raskó, Tamás; Tichý, Boris; Mikulasek, Kamil; Tsagiopoulou, Maria; Oppelt, Jan; Kastrinaki, Georgia; Lefaki, Maria; Singh, Manvendra; Zink, Annika; et al. (Redox biology, 2020)
Spinocerebellar ataxia type-1 (SCA1) is caused by an abnormally expanded polyglutamine (polyQ) tract in ataxin-1. These expansions are responsible for protein misfolding and self-assembly into intranuclear inclusion bodies (IIBs) that are somehow linked to neuronal death. However, owing to lack of a suitable cellular model, the downstream consequences of IIB formation are yet to be resolved. Here, we describe a nuclear protein aggregation model of pathogenic human ataxin-1 and characterize IIB effects. Using an inducible Sleeping Beauty transposon system, we overexpressed the ATXN1(Q82) gene in human mesenchymal stem cells that are resistant to the early cytotoxic effects caused by the expression of the mutant protein. We characterized the structure and the protein composition of insoluble polyQ IIBs which gradually occupy the nuclei and are responsible for the generation of reactive oxygen species. In response to their formation, our transcriptome analysis reveals a cerebellum-specific perturbed protein interaction network, primarily affecting protein synthesis. We propose that insoluble polyQ IIBs cause oxidative and nucleolar stress and affect the assembly of the ribosome by capturing or down-regulating essential components. The inducible cell system can be utilized to decipher the cellular consequences of polyQ protein aggregation. Our strategy provides a broadly applicable methodology for studying polyQ diseases.
Keywords: oxidační stres; proteiny nervové tkáně; Nerve Tissue Proteins; jaderné proteiny; lidé; intranukleární inkluzní tělíska; Oxidative Stress; Nuclear Proteins; Ataxin-1; ataxin-1; Humans; Intranuclear Inclusion Bodies